2000
DOI: 10.1016/s0044-8486(00)00316-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia on growth and metabolism of juvenile turbot

Abstract: The effects of hypoxia on growth, feed efficiency, nitrogen excretion, oxygen consumption and metabolism of juvenile turbot (120 g) were studied in a 45-day experiment carried out in sea water at 17.0±0.5°C and 34.5 ppt salinity. Fish were fed to satiation at O2-concentrations of 3.5±0.3, 5.0±0.3 mg l−1 (hypoxia) and 7.2±0.3 mg l−1 (normoxia). Both feed intake (FI) and growth were significantly lower under hypoxia than under normoxia, with no significant differences being observed between 3.5 and 5.0 mg O2 l−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(83 citation statements)
references
References 25 publications
7
74
0
1
Order By: Relevance
“…When exposed to hypoxic shocks, fish ate less than corresponding groups: 14% and 18% less than in normoxic and moderate hypoxic water, respectively. It has previously been shown that in turbot reared under adverse environmental conditions (oxygen depletion or ammonia accumulation), growth decrease was primarily explained by a decrease in FI (Person-Le Ruyet et al, 1997;Pichavant et al, 2000Pichavant et al, , 2001. In turbot farms, FI is also affected by environmental conditions, for example, by changes in O 2 concentration (Mallekh and Lagardère, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When exposed to hypoxic shocks, fish ate less than corresponding groups: 14% and 18% less than in normoxic and moderate hypoxic water, respectively. It has previously been shown that in turbot reared under adverse environmental conditions (oxygen depletion or ammonia accumulation), growth decrease was primarily explained by a decrease in FI (Person-Le Ruyet et al, 1997;Pichavant et al, 2000Pichavant et al, , 2001. In turbot farms, FI is also affected by environmental conditions, for example, by changes in O 2 concentration (Mallekh and Lagardère, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The daily feed restricted ration was equal to the mass of food ingested per fish of the 100-20 group. The hypoxic tanks were supplied with O 2 deprived water obtained by the injection of nitrogen to remove the desired amount of oxygen using an oxygen depletion system described by Pichavant et al (2000). Oscillating O 2 concentrations were created by manipulating the water supply without changing the water flow rate: the initial water supply (100% or 75% air saturation water) was abruptly switched for 20% air saturation water.…”
Section: Long-term Experimentsmentioning
confidence: 99%
“…Oxygen partial pressure in water (PwO 2 ) levels were adjusted by means of an oxygen-depletion system described in Pichavant et al (2000). In each experimental box, PwO 2 was continuously monitored throughout the experiment according to Gaumet et al (1995).…”
Section: Fish and Conditioningmentioning
confidence: 99%
“…Food intake decreased significantly in Atlantic cod (Gadus morhua) and rainbow trout (Oncorhynchus mykiss) held at 60% water oxygen saturation (Chabot & Dutil, 1999;Neji, Naimi, Lallier & De La Noüe, 1991). Reduced food consumption results in growth impairment for juvenile turbot (Scopthalmus maximus) and Europen sea bass (Dicentrarchus labrax) in DO less than 3.5 mg/L (Pichavant, Person-Le-Ruyet, Le Bayon, Sévère, Le Roux & Boeuf, 2001;Pichavant, Person-Le-Ruyet, Le Bayon, Sévère, Le Roux, Quéméner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%